Behind the invasion of Iraq (Monthly Review Press, 2003)
""This book contributes significantly ot the conversation seeking to understand the international forces at play in the threatening war on Iraq.""--Nelson Mandela. ""Behind the Invasion of Iraq . . .synthesizes the seemingly disparate threads of the U.S. war drive in a blistering indictment of American foreign policy . . .The effect is of puzzle pieces clicking into place.""-Counterpunch. Since September 11, 2001, there have been many accounts of the ways in which the alignment of global power is changing or will be changed by the U.S.'s ""war on terrorism."" Most of them take as their star.